A CONCEPTUAL STUDY OF LECTURER PERFORMANCE: THE IMPACT OF FINANCIAL INCENTIVES, TRAINING, WORK EXPERIENCE, AND TECHNOLOGY INTEGRATION - Khairunnisa Ahmad Mokhtar; Wan ‘Aliaa Wan Anis; Siti Noorjannah; Aliaa Diyana Zamri Anis; Farah Lina Azizan (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Lecturer performance plays a vital role in determining the quality of education and the success of educational institutions. Although digital tools are becoming an essential part of higher education, the effect of technology on training and teaching effectiveness has not been fully examined. This study explores the factors influencing lecturer performance in public universities in Northern Malaysia, focusing on the interaction between financial incentives (compensation), professional development opportunities (training), external work experience (labor market experience), and technology integration in driving lecturers’ motivation and engagement. By synthesizing existing literature, this conceptual study aims to create a comprehensive framework for understanding lecturer performance. The findings provide valuable insights into how these factors interact within the context of public universities in Northern Malaysia, offering important implications for policymakers and university administrators who strive to improve lecturer performance and foster better educational outcomes.